Book video content: towards а question of multimodality of the mediatised literary field - Makarova, Anastasija (Vilnius University Open Series, 2024)
The article deals with the specificity of new forms of communication in the modern mediatised literary field. The author reveals the problematics of book video content functioning as a metatext centred around a literary text. On the examples of book blogs posted in the platforms TikTok and YouTube, the features of book video content through the prism of multimodality are considered. The author concludes that the ability to post video content allows bloggers, through the use of multimodality, to interpret books in a creative way. However, the book recommendation video content on TikTok and YouTube is specific.
Keywords: book content; book recommendations; TikTok; YouTube